AN IMPROVED METHOD OF MANUFACTURING A COMPLETE REMOVABLE PLATE PROSTHESIS UNDER THE CONDITION OF INTOLERANCE TO ACRYLIC PLASTIC IN PATIENTS (American Journal of Pedagogical and Educational Research, 2023)
An original solution for the removal of completely missing teeth with intolerance to acrylic prostheses is presented. A reinforced full removable prosthesis made of polypropylene has been developed. Clinical trials have shown the advantages of the proposed method in comparison with the most common similar products.